Microstructure and mechanical properties of B4C–TiB2–SiC composites toughened by composite structural toughening phases. Issue 7 (30th March 2017) - Zhang, Xiaorong; Zhang, Zhixiao; Wang, Weimin; Shan, Junhong; Che, Hongwei; Mu, Jingbo; Wang, Guangsuo
Abstract: B4 C–TiB2 –SiC composites toughened by composite structural toughening phases, which are the units of (TiB2 –SiC) composite, were fabricated through reactive hot pressing with B4 C, TiC, and Si as raw materials. The units of (TiB2 –SiC) composite with the size of 10‐20 μm are composed of interlocking TiB2 and SiC with the size of 1‐5 μm. The addition of TiC and Si can effectively promote the sintering of B4 C ceramics. The relative densities of all the B4 C composites with different contents of TiB2 and SiC are close to completely dense (98.9%‐99.4%), thereby resulting in superior hardness (33.1‐36.2 GPa). With the increase in the content of TiB2 and SiC, the already improved fracture toughness of the B4 C composite continuously increases (5.3‐6.5 MPa·m 1/2 ), but the flexure strength initially increases and then decreases. When cracks cross the units of the (TiB2 –SiC) composite, the cracks deflect along the interior boundary of TiB2 and SiC inside the units. As the crack growth path is lengthened, the crack propagation direction is changed, thereby consuming more crack extension energy. The cumulative contributions improve the fracture toughness of the B4 C composite. Therefore, the composite structural toughening units of the (TiB2 –SiC) composite play an important role in reinforcing the fracture toughness of the composites.